State and Environment : The Comparative Study of Environmental Governance - Duit, Andreas (Book collections on Project MUSE., 2014)
This volume of comparative studies documents the continuing relevance of the state in environmental politics and policy. The book also demonstrates the analytical power of the comparative approach to the study of environmental politics and policy, offering cross-national comparisons of environmental governance in both developed and developing countries. Some chapters are based on qualitative studies from a small number of countries; others offer statistical analyses of quantitative data from many more countries over a longer time period.